The Relationship between Optimal Size of Government and Economic Growth: Empirical Evidence from Turkey, Romania and Bulgaria - Altunc, O. Faruk; Aydin, Celil (ELSEVIER SCIENCE BV, 2013)
In this study the relationship between government expenditure and rate of economic growth will be analyzed for Turkey, Romania and Bulgaria by using the data for the period 1995-2011. The main purpose of this study is to test whether there is an "inverted U" shape relationship between public spending and economic growth or not, and to find the optimal level of public spending for Turkey, Romania and Bulgaria economies. Theoretically, the relationship between optimal government expenditure and economic growth has been associated with Armey curve. Armey Curve, propounded by Richard Armey, is one of the tools that developed to demonstrates the role of the state in the economic process. The basic logic behind the Armey Curve is that the relationship between public spending and gross domestic product (GDP) is positive up to a certain point, thereafter the relationship becomes negative. According to Friedman (1997), the government has an important role in a free and open society. It is emphasized that, average contribution of the public sector in the economy is positive, but as the public share of national income increases from 15% to 50% the marginal contribution of the public sector will be negative. Therefore, Friedman advocates that based on development level of countries, the optimal level of public spending should be between 15% and 50%. The econometric method using in this study is ARDL bound testing approach developed by Paseran et al. (2001). Empirical findings show that the share of present public expenditure in GDP exceeds optimal public expenditure for three countries. Based on the results of the study, an economic policy proposal may be that the share of public expenditure should be reduced and the effectiveness of public expenditure programs should be increased. (C) 2013 The Authors. Published by Elsevier Ltd.
Lumen 3rd International Conference on Logos Universality Mentality Education Novelty (LUMEN) - Current Paradigms in Social Sciences -- APR 10-13, 2013 -- Iasi, ROMANIA
Keywords: Public Sector; Armey Curve; ARDL Bounds Testing Approach